Diabetic hepatosclerosis: another diabetes microvascular complication?. Issue 2 (18th January 2016) - King, R. J.; Harrison, L.; Gilbey, S. G.; Santhakumar, A.; Wyatt, J.; Jones, R.; Bodansky, H. J.
Abstract: Background: Liver disease in diabetes is common and is frequently the result of hepatic steatosis. Diabetic hepatosclerosis is a relatively recent description of sinusoidal fibrosis, without steatosis, observed in liver biopsies of people with diabetes presenting with cholestasis. Its association with other microvascular complications suggests it is a form of hepatic diabetic microangiopathy. Case report: We report the case of a 50‐year‐old woman with longstanding Type 1 diabetes, complicated by nephropathy resulting in cadaveric renal transplant, retinopathy, gastroparesis and neuropathy with slowly healing ulceration to her right foot. She was noted to have deranged liver function tests: alanine aminotransferase, 162 IU/l; bilirubin, 44 IU/l; alkaline phosphatase, 5279 IU/l (isoenzymes; bone 1029 IU/l, liver 4250 IU/l); γ–glutamyl transferase, 662 IU/l. A non‐invasive liver screen did not reveal the cause of the cholestasis. A liver biopsy demonstrated sinusoidal fibrosis without evidence of steatosis and thus a diagnosis of diabetic hepatosclerosis was made. Comparison with a biopsy performed 11 years previously at a different trust due to elevated alkaline phosphatase levels revealed slow progression of the sinusoidal fibrosis. Discussion: This case describes the longest reported clinical course of diabetic hepatosclerosis, spanning 11 years, in which time the patient did not develop evidence of cirrhosis or portal hypertension. It is difficult to estimate the clinical relevance of this condition because little is known regarding its clinical course and effect on morbidity and mortality. Identified patients should undergo low‐intensity, long‐term follow‐up to improve understanding of its clinical sequelae and relevance.